PERSONAL BEHAVIOR: KEMAMPUAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT KPUD KABUPATEN BUNGO - Roni, Khairun A; Supriyati, Supriyati (Universitas Putra Indonesia YPTK Padang, 2015)
AbstractThis research aims to find out the effect of work ability and work environment towardpersonal ability.. The subject of this research is 39 employees of KPU distric of Bungo. Theresult of this research from multiple regression showed Y = 2.168 + 0,341X1 +0,019X2 +e.Based on above calculation, can be concluded that simultaneously and partially theindependent variable of work ability (X1), work environment (X2) have significant effect ondependent variable that is the employee working ability (Y).Keywords: working ability; work environment ;employee ability